Penguatan UMKM Produk Herbal melalui Penerapan Proses Produk Halal dan Pemasaran Digital - Prihastiwi, Diah Agustina; Astutik, Erni Puji (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The decades-old herbal products are one of the potentials owned by Trasan Village, Bandongan District, Magelang Regency. Because of the products’ perceived efficacy, their longevity is assured. The products have not received halal certification, thus one of the issues these businesses face is that marketing is still done by going door-to-door. Thus far, halal goods and equipment have been used in the traditional production of herbal products. On the other hand, the UMKM owners will have more chances to grow the marketing network if the products have received halal certification. Additionally, the owners hope to grow their company by reaching a larger market with herbal items. Thus, to increase market penetration, digital marketing training is required. This community service program aims to support traditional herbal product producers with digital marketing and the implementation of the halal product process. Giving training and supervision on the halal certification procedure for UMKM owners and the usage of suitable digital marketing constitutes this community service. Partners receive training on the benefits of registering halal items, the necessity of a halal product certification process, and how to use digital marketing tools. Herbal product entrepreneurs can identify and fulfil the requirements for the halal product process and implement marketing strategies by using digital media with the help of the training and mentorship programs offered. The result of this program showed an increase in the quantity and value of the products. Sales of herbal products have now spread to Yogyakarta due to the increasingly wide marketing area and increasing customer trust in the quality and halal-ness of the products.